SECURITY BREACH INCIDENCES OF SACCOS WITH OR WITHOUT SECURITY POLICY WITH A BROAD SCOPE: A CASE OF SACCOS IN KENYA - Sirma, Jerotich; Raburu, George; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
The risks that organizations face include safeguarding information resources in their networks.Organizations have formulated security policies with the hope of solving the problem of securitybreaches or to significantly reduce incidences of security breaches. However, systems are stillvulnerable to security breaches. The vulnerability may arise from security breaches that could beinternal or external to the organization. A security breach can result in the risk of an intrusioninto the SACCOS’ sensitive information. For example, an intruder can potentially gain access toSACCOS client documents that may contain propriety financial information. Disclosure ofclient information can result in the loss of confidence in SACCOS and real financial loss.Despite the identification of good security policies and frameworks for security governance inthe information systems field, there is still lack of understanding by users about how securitybreach incidents have the potential to weaken the implementation of security policies in theSACCOS sector. The study will try to fill in the gap upon reporting the results of the study thatsought to analyze the relationship between information security policies and the incidences ofsecurity breaches in the SACCOS sector in Kenya.